Peer Support as a Direct Benefit of Focus Group Research: Findings from a Secondary Analysis - Forchuk, Cheryl (International Journal of Psychosocial Rehabilitation, 2015)
Peer support among individuals living with mental illness can occur in formal or informal settings and result in the exchange of knowledge and acceptance. The purpose of this study is to explore peer support dynamics that spontaneously emerged within focus groups with psychiatric survivors. Thirty-four psychiatric survivors participated in focus groups as part of a mixed method research project examining poverty and mental health. A secondary supplementary analysis of the focus group data was conducted to examine instances of peer support that emerged among participants. Participants engaged in peer support in a number of ways, including the exchange of practical information, evaluation of information and services, provision of empathy and affirmation, and development of friendships. Participants noted the value of gaining information from and supporting one another. The results demonstrate that psychiatric survivors can experience personal benefits through participation in research, including the development of informal peer support relationships.